INTRODUCTION OF REOG PONOROGO CULTURE TO STIMULATE PATRIOTISM FOR 3-4 YEARS OLD CHILDREN - Uliasari, Nita; Dian Kristiana (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to examine the impact of introducing Ponorogo culture on the formation of love for the country in early childhood, especially children aged 3-4 years. Culture is an important element in a nation's identity and has great potential to form love for one's country from an early age. This research uses observation and interview methods. The results of the research show that the introduction of Ponorogo culture has a positive impact on the formation of love for the country in young children at POCENTER (Ponorogo Early Education Center). Children are introduced to various aspects of Ponorogo culture. Reyog Ponorogo. This research recommends further efforts in developing early education programs that incorporate local cultural elements, such as Ponorogo culture, to help children develop love and loyalty towards their homeland from an early age. It is hoped that this can be an important contribution in building a generation that loves its homeland and has a strong cultural identity.